Female-specific perspectives in social work research in sub-Saharan Africa : literature review - Laine, Elina; Anis Merja (Routledge, 2025)
In this article, the focus is on social work in sub-Saharan Africa from a female-specific perspective. The article answers the following two questions: what are the most central questions around female-specific perspectives in social work research in sub-Saharan Africa and what kind of emphasis does social work have or recommend for working with women? The aim is to provide international dialogue and new openings for Nordic social work research and practice. The analysis is based on data collected by conducting an integrative literature review. The results show that the importance of women´s perspectives in sub-Saharan Africa is an issue linked to gendered poverty, inequality and gender-based violence. The included studies deal with health issues, including maternal health, sexual health and reproductive health. Social work emphasizes measures based on spirituality and communities, where a female-specific perspective is understood as part of communal structures. An analytical examination of social work in African countries can develop Nordic social work practice and the discipline so that it considers the meaning of female-specific issues as part of communal resources, spiritual practices and global inequality.